(untitled) (Al-Wasatiyah: Journal of Religious Moderation, 2024)
The verses of the Qur’an interpreted by the mufassirs continue to develop. This is done to achieve the goal of the Qur’an which is ṣholi ḥ li kulli zaman wa makan. It is not surprising that the methods of interpreting the Qur’an are very diverse in order to obtain variations in the meaning of the Qur’an in an integrative manner. This study focuses on the meaning of Jihad contained in the surah alAnkabut / 29: 69. This study discusses the interpretation of two hermeneutical figures, Sahiron Syamsuddin and Nasr Hamid Abu Zayd. The questions to be studied are how do the two figures think in interpreting the verses of jihad and how is the correlation between the hermeneutical interpretation of the verses of jihad and Wasathiyah Islam? The method used is the comparative method, with a combined approach between phenomenology and critical discourse analysis. The results of this study reveal that both figures deny the existence of textual interpretations of the verses of jihad that are only related to the context of warfare. According to Syamsuddin, the meaning of jihad in Surah al-Ankabut/29:69 can be seen in three stages: first, jihad against one’s own lusts. Second, jihad against those closest to us. Third, jihad against the government, state, and homeland. Meanwhile, Zayd through his hermeneutics (tafsir alsiyaqi) explains that the meaning of jihad in Surah al-Ankabut/29:69 is to free the state from all its problems. The conclusions of the two figures are relevant to the discourse of Islamic wasathiyyah, because they offer an inclusive, contextual, and relevant perspective on the verses of jihad, so that they are able to answer the challenges of the modern world, including issues such as radicalism, global injustice, and strengthening current humanitarian values.